2018
DOI: 10.18203/2349-2902.isj20184091
|View full text |Cite
|
Sign up to set email alerts
|

A study on clinicopathology of fistula in ano

Abstract: Background: Perianal fistula is a common surgical problem which poses great discomfort to patients and causes prolonged morbidity when improperly managed or developed complications. Its management protocols are ill defined, and the efficacy of newer treatment modalities are not well established. The aim of the study was to study the clinicopathology of Perianal fistula and its prognostic factors.Methods: This was a prospective study conducted at the Department of General Surgery, Rajiv Gandhi Government Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…This incidence is slightly elevated in comparision to other Indian study like Khanna et al who cited an incidence of 14.7%. 12 The rate of frequency cited above may indicate that there is a increase in incidence which may be attributed to patient's growing awareness about the disease and about their health.…”
Section: Resultsmentioning
confidence: 99%
“…This incidence is slightly elevated in comparision to other Indian study like Khanna et al who cited an incidence of 14.7%. 12 The rate of frequency cited above may indicate that there is a increase in incidence which may be attributed to patient's growing awareness about the disease and about their health.…”
Section: Resultsmentioning
confidence: 99%
“…Internal opening was identified in (26.53%). Phinehas E et al observed internal opening only 45.33%, of patients [20] . On fistulogram, tract was identified (55.11%) and not identified (44.89%) & compared intra-op findings with length of tract, fistulogram report correct in (22.44%).…”
Section: Methodsmentioning
confidence: 94%
“…Saadeldin Ahmed idris et al observed anal discharge 99%, pain 57.5%, Itching 43.4%, Bleeding 3.8%, Constipation (14.2%) [19] . Phinehas E et al stated Perianal discharge 56.67%, external opening seen in all (100%) [20] . Van Koperen PJ et al described small, painful anal swelling with intermittent sero-purulent discharge [6] .…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations